Investigation of Adverse‐Event‐Related Costs for Patients With Metastatic Breast Cancer in a Real‐World Setting. (1st August 2014) - Hurvitz, Sara; Guerin, Annie; Brammer, Melissa; Guardino, Ellie; Zhou, Zheng‐Yi; Latremouille Viau, Dominick; Wu, Eric Q.; Lalla, Deepa
Abstract : Background: Existing treatments for metastatic breast cancer (mBC) are often effective but can cause adverse events (AEs). This study aimed to identify AEs associated with chemotherapies commonly used in mBC treatment (phase 1) and to quantify the economic impact of these AEs (phase 2). Materials and Methods: Patients in phase 1 had at least one claim for therapy for mBC, with at least one episode with single or multiple agents. The most common chemotherapy‐related complications were identified using medical and pharmacy claims data. In phase 2, patients meeting study criteria were divided into four treatment cohorts by the line of treatment and chemotherapy received: first‐line taxane‐treated patients, second‐line taxane‐treated patients, first‐line capecitabine‐treated patients, and second‐line capecitabine‐treated patients. Average monthly AE‐related health care costs per cohort were stratified by cost component. Total monthly costs per number of AEs were also calculated. Results: On average, patients in phase 1 ( n = 1, 551) had 2 episodes of treatment, with a mean duration of 131 days. The most frequently noted complications were anemia (50.7% of mBC treatment episodes), bilirubin elevation (26.4%), and leukopenia (24.8%). In phase 2, costs related to AEs were primarily driven by incremental inpatient, outpatient, and pharmacy costs. Increases in average monthly costs ranged from $854 (9.0%) to $5, 320 (69.5%), according to cohort. Overall costs increased with increasing numbers of AEs. Conclusion: Chemotherapy‐related AEs in patients with mBC are associated with a substantial economic burden that increases with the number of AEs reported. Abstract : This study aimed to identify adverse events (AEs) associated with chemotherapies commonly used in metastatic breast cancer (mBC) treatment and to quantify the economic impact of these AEs. Results showed that chemotherapy‐related AEs in patients with mBC are associated with a substantial economic burden that increases with the number of AEs reported.